Влияние различных агрометеорологических условий на фотосинтез гороха - Иконникова, В.В. (Культура народов Причерноморья, 2013)
Рассматривается влияние различных агрометеорологических условий на интенсивность
фотосинтеза гороха. Процессы фотосинтеза, дыхания, роста в агрометеорологических расчетах
описываются с помощью динамических моделей продукционного процесса растений. Однако все эти
модели основаны на аппроксимированных результатах эмпирических исследований, на отдельных
территориях по отдельным культурам и предназначены для реализации конкретных целей. Получена
количественная оценка влияния солнечной радиации, температуры воздуха, влагообеспеченности, при
которых интенсивность фотосинтеза гороха достигает максимальных значений. Розглядається вплив різних агрометеорологічних умов на інтенсивність фотосинтезу
гороху. Процеси фотосинтезу, дихання, росту в агрометеорологічних розрахунках описуються за
допомогою динамічних моделей продуційного процесу рослин. Проте всі ці моделі засновані на
апроксимованих результатах емпіричних досліджень, на окремих територіях по окремих культурах і
призначені для реалізації конкретних цілей. Отримана кількісна оцінка впливу сонячної радіації,
температури повітря, вологозабезпеченості, при яких інтенсивність фотосинтезу гороху досягає
максимальних значень. The influence of the different agro-meteorological conditions on the rate of photosynthesis of pea.
Plant development and yield formation - this is a very complex set of a number of physiological processes
associated with environmental factors. The processes of photosynthesis, respiration, growth in the agrometeorological
calculations are described using dynamic models of the production process of plants. Dynamic
models of growth and development of leguminous crops in some way a good description of the specific features
of physiological processes in plants. However, all these models are based on the approximate results of
empirical research in selected areas for some crops and are designed for specific purposes, so the application of
any of them for legume crops need to be very careful . The main processes , which are formed as a result of plant
biomass is photosynthesis and respiration. The productivity of photosynthesis is determined by the agrometeorological
factors, which are constantly changing during the growing season. At a certain stage of
development of the plant photosynthesis productivity per unit area of leaves under given lighting conditions
depends on the agro-meteorological conditions, namely the temperature and moisture conditions with the help of
numerical experiments determined the effects of different features of agro-meteorological conditions on the rate
of photosynthesis . Obtain quantitative estimates of the effect of solar radiation, air temperature, moisture
content at which the rate of photosynthesis of pea is highest.